IN THE TREND OF THE 21st CENTURY: BIOLOGY AND BIOMEDICINE - Alexey V. Sem'yanov; Viktor B. Kazantsev (Высшее образование в России)
The article dwells on the history of a new Institute of Biology and Biomedicine that was established at Lobachevsky State University of Nizhni Novgorod on the basis of the UNN Faculty of Biology and its biology research institutes. The purpose of the reorganization was to modernize the educational process with a focus on biomedicine and to develop biomedical research. The authors substantiate the strategy for inviting professors from leading universities in the world to give lectures and conduct research at IBBM on part-time basis. The role of visiting scholars in attracting extra-budgetary funding and improving the quality of scientific publications is discussed.